Systematic Literature Review Comparative Analysis Factors Influencing the Success of Enterprise Systems - Ryo Pambudi; Dinda Ayu Aprilia; Eko Sediyono; Aris Puji Widodo (Sistemasi: Jurnal Sistem Informasi, 2022)
Enterprise System (ES) is a software system that helps companies operate their businesses and manage their data. The importance of achieving ES adaptation to the organization's business behavior requires a systematic effort to measure the success factors in enterprise systems so that the objectives of using ES can be achieved. Some journals examine several factors that influence the success of enterprise system.  Analysis needs to be carried out as a basis and consideration to produce measurement methods that continue to develop so as to encourage the emergence of various new successful system measurement models. Analysis and evaluation of the success factors that influence the success factors of ES can be done using Systematic Literature Review (SLR) method. This study uses the SLR method of comparison of success factors in ES, which includes journals published from 2000 to 2022. From the results of this SLR research, it can be seen that several success factors influence the success of the enterprise system.